Uso de acidificante para otimização da adubação fosfatada em solo de reação alcalina na cultura da melancia irrigada - Silva, Max Venicius Teixeira da (2020)
In the Rio Grande do Norte, the watermelon has been of great importance due to the edaphoclimatic characteristics and the favorable consumer market, where it has ceased to be a crop explored only in the rainy season, with the purpose of supplying local markets, to become a local crop. technified production activity for both domestic and foreign markets. The research was carried out in two seasons, September to November 2017, and August to October 2018, in the Roçado Grande farm, Upanema-RN. The objective of this work was to evaluate the application of elemental sulfur associated to phosphate fertilization in a cambisol with and without historical irrigated cultivation in the watermelon crop in the region of Mossoró-RN. The adopted design was in randomized blocks in a factorial scheme of 4x3. In the first experiment, using the cultivar Magnum, the treatments consisted of 4 phosphorus doses (0, 30, 60, 90 kg ha-1 of P2O5) and 3 sulfur doses (0, 250 and 500 kg ha-1 of S ), in the second experiment with cultivar Quetzali, 4 doses of phosphorus (0, 30, 70 and 110 kg ha-1 of P2O5) and 3 doses of sulfur (0, 250 and 500 kg ha-1 of S) were applied. Magnum watermelon obtained maximum commercial yield at 60.7 kg ha-1 of P2O5 in the soil without cultivation history, and 62.5 kg ha-1 of P2O5 in the soil with cultivation history. reduction of values. Regarding total yield, the highest values were observed at intermediate doses of phosphorus (30 and 60 kg ha-1 of P2O5) combined with the lowest sulfur doses (0 and 250 kg ha-1 of S). Phosphorus doses statistically influenced all fruit quality variables except pulp pH, although all fruits obtained the ideal consumer market acceptance ranges. Phosphorus rates influenced commercial yield of the quetzali cultivar, with watermelon plants obtaining maximum values ranging from 45 to 53 t ha-1 in the soil with and without irrigated cultivation history. Sulfur application did not influence the total yield of the cultivar quetzali, since the highest values were observed at 0 kg ha-1 dose of S. The fruit quality variables were influenced by the treatments, except for the pulp pH, however. the values observed in the analyzes were within the market acceptance range. Increasing doses of phosphorus caused an increase in soil pH, while acidifying reduced